Proyeksi Perkembangan Perkoperasian 2019 - Muhamad Ardi Nupi Hasyim; Heri Nugraha; Eka Setiajatnika; Fitriana Dewi Sumaryana (Gorontalo Development Review, 2019)
This article aims to determine the development of cooperatives in West Java at present, projections of the development of cooperatives in West Java in 2019 and the contribution of cooperatives to the economy of West Java.  The research methods used are explanatory research, data collection conducted by surveys, interviews, observations, and FGD and using a simple regression analysis approach of secondary data sourced from BPS, Kemenkop , Dinas KUKM West Java province. The results of the study show that the condition of cooperatives in terms of quantity in West Java can now be said to deteriorate. Inactive cooperatives are far more than active cooperatives. Whereas in previous years, namely in 2015-2017 active cooperatives dominated more than inactive cooperatives and West Java cooperative contributions to state revenues were still relatively small.